CARE SYSTEMS IN MOTOR VEHICLES IN THE CAR & MOTOR SAVE WITH COMPUTERIZED - Tri Aryati Paksi; Linda Wahyu Widianti, Skom, MMSI. (Jurnal Sistem Informasi, 2005)
Current technological development has become a very important part of human life invarious fields so that makes a man found a way to simplify the job. Development wasexpected to present a more interesting information like the existence of various kindsof animation, hear the voices and images. In this case the multimedia was a newtechnology in the field of information that can assist and provide easiness in progressvisually oriented.This concept is expected to help Maya 5.4 provides information on the type of carwith a more attractive appearance in the form of short films that are finally able tohelp choose a car according to desired taste.